Comparative Study of Transplantation of Hepatocytes at Various Differentiation Stages into Mice with Lethal Liver Damage - Ryo Kamimura; Takamichi Ishii; Naoya Sasaki; Masatoshi Kajiwara; Takafumi Machimoto; Michiko Saito; Kenji Kohno; Hirofumi Suemori; Norio Nakatsuji; Iwao Ikai; Kentaro Yasuchika M.D., Ph.D.; Shinji Uemoto (Cell Transplantation, 2012)
Hepatocyte transplantation utilizing induced pluripotent stem cells (iPSCs) or embryonic stem cells (ESCs) has been expected to provide an alternative to liver transplantation. However, it remains uncertain precisely which cell type is the best suited for cell transplantation. In particular, it is unclear whether mature hepatocytes, which have sufficient liver function, or immature hepatic progenitor cells, which have a higher proliferative capacity, will provide a better outcome. The main objective of this study was to investigate the therapeutic efficacy of the transplantation of hepatocytes at various differentiation stages. We utilized transgenic mice that expressed diphtheria toxin (DT) receptors under the control of an albumin enhancer/promoter. ESC-derived endodermal cells, fetal hepatocytes, and adult hepatocytes were transplanted into these mice with experimentally induced lethal acute liver injury caused by DT administration. The transplanted cells were marked by enhanced green fluorescent protein. We evaluated their effects on survival. At 35 days after transplantation, the survival rate of the adult hepatocyte-transplanted group (8/20, 40%) was significantly improved in comparison to that of the sham-operated group (2/25, 8%), the fetal hepatocyte-transplanted group (1/20, 5%), and the ESC-derived endodermal cell-transplanted group (0/21, 0%). The adult hepatocytes proliferated in the recipient livers and replaced a large part of their parenchyma. The transplantation of adult hepatocytes for acute liver failure significantly improved the survival rate in comparison to that of transplantation of immature cells, thus suggesting that ESCs and iPSCs should be differentiated into mature hepatocytes before cell transplantation for acute liver failure.